Analytical application of carbon dot-based molecularly imprinted polymers in the fabrication of selective fluorescence and electrochemical sensors – a review - Ng'andu, Clever; Nsibande, Sifiso A. (Talanta (Oxford), 2026)
Carbon quantum dots (CQDs) offer unique chemical and optical properties which have led to their adoption in designing chemical sensors for environmental and biological applications. They have several advantages over heavy metal-based quantum dots, including low toxicity and biocompatibility, which have made them attractive for researchers. They can also be modified and incorporated with molecularly imprinted polymers (MIPs) to fabricate highly selective composite materials for the determination of target analytes. In this work, we first make a case for this specific review in the literature, considering other reviews that have been published on this subject. Then, we briefly introduce the reader to commonly used strategies for the synthesis of CDs and CD-MIPs for selective optical and electrochemical sensor fabrication. Subsequently, we discuss recent research advancements in the synthesis and application of these sensors across various matrices, with an emphasis on the determination of biologically relevant analytes, environmental monitoring, and food safety and quality assessment. Ultimately, key findings are highlighted, and future perspectives for this field are shared. [Display omitted] •Preparation of carbon dots modified with molecularly imprinted polymers (CD-MIPs) for chemosensing.•Analytical performance of the fluorescence and electrochemical sensors with CD-MIP recognition units.•Applications of the CD-MIP sensors in food analysis, environmental monitoring, and sensing of biorelevant compounds.•Challenges and prospects of chemosensors with CD-MIP recognition units.